Periorbital Necrotizing Fasciitis: Case Presentation - Ryan S Huang; Nikhil S Patil; Yasser Khan (Interactive Journal of Medical Research, 2023)
Necrotizing fasciitis (NF) is an aggressive and potentially life-threatening infection of the superficial fascia and surrounding skin, fat, fascia, muscle, and other soft tissue structures. Here, we outline the rare case of a 26-year-old man with a periorbital Streptococcus pyogenes A NF infection. Our case report underscores a unique instance of periorbital NF, distinctively presenting without any predisposing risk factors, shedding light on its presentation, treatment, and pathophysiology.